Lithium/Sulfur Batteries Upon Cycling: Structural Modifications and Species Quantification by In Situ and Operando X‐Ray Diffraction Spectroscopy. Issue 16 (15th May 2015) - Waluś, Sylwia; Barchasz, Céline; Bouchet, Renaud; Leprêtre, Jean‐Claude; Colin, Jean‐François; Martin, Jean‐Frédéric; Elkaïm, Erik; Baehtz, Carsten; Alloin, Fannie
<x xml:space="preserve">Abstract</x> A quantitative analysis of in situ and operando X‐ray diffraction studies allows for deeper insight into the mechanism of Li2S formation and consumption. A two‐step reaction process is proposed for both discharge and charge. Changing selectivity for Li2S formation is estimated, with solely Li2S being formed during the earliest step, followed by possible concurrent formation of Li2S2 intermediate in the further step of discharge.